Keragaan Genetik dan Pendugaan Heritabilitas pada Komponen Hasil dan Kandungan β-Karoten Progeni Kelapa Sawit - Lollie Agustina P. Putri; , Sudarsono; Hajrial Aswidinnoor; Dwi Asmono (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2009)
An experiment to study heritability, general combining ability (GCA), and specific combining ability (SCA) of some traits in oil palm progeny was conducted at Kebun Surya Adi, PT. Bina Sawit Makmur, Sampoerna Agro, Ogan Komering Ilir, Sumatera Selatan, from July 2006 until September 2008.  The research was arranged in alpha design with two replications, 50 progenies and 12 palms for each replication, respectively. The results showed that broad sense heritability estimates were high for mesocarp to fruit, oil to fresh mesocarp, and  kernel to fruit content ratios, and β-carotene content; medium for bunch number and oil to bunch ratio; and low for fresh bunch and fruit to bunch ratio. The general combining ability (GCA) of bunch number, mesocarp to fruit, oil to fresh mesocarp, and kernel to fruit ratios and β-carotene content were highly significant. Similarly, the specific combining ability (SCA) of mesocarp to fruit, oil to fresh mesocarp, and kernel to fruit ratios and β-carotene content were also highly significant.   Key words:  Heritability, combining ability, Elaeis guineensis Jacq., alpha design, β-carotene